Zurich tax handbook 2010-11 - Macpherson, L.; Foreman, Anthony (Pearson Education Limited, 2010)
This tax handbook covers every aspect of taxation in a totally accessible manner, providing worked examples, checklists and shrewd advice in the form of tax-saving tips